Integration of ERT, IP and SP Methods in Hard Rock Engineering - Peng Shao (MDPI AG, 2021)
Investigation of a hard rock site for the development of engineered structures mainly depends on the delineation of weathered and unweathered rock, and the fractures/faults. Traditionally, borehole tests are used in such investigations. However, such approaches are expensive and time-consuming, require more equipment, cannot be conducted in steep topographic areas, and provide low coverage of the area with point measurements only. Conversely, geophysical methods are non-invasive, economical, and provide large coverage of an area through both vertical and lateral imaging of the subsurface. The geophysical method, electrical resistivity tomography (ERT), can reduce a significant number of expensive drilling tests in geotechnical investigations. However, a geophysical method alone may provide ambiguity in the interpretation of the subsurface, such as electrical resistivity cannot differentiate between water and clay content. Such uncertainty can be improved by the integration of ERT with induced polarization (IP). Similarly, self-potential (SP) can be integrated with other geophysical methods to delineate the groundwater flow. In this contribution, we integrated three geophysical methods (ERT, IP and SP) to delineate the weathered and unweathered rock including the weathered/unweathered transition zone, to detect the fractures/faults, and to map the groundwater flow. Based on ERT, IP and SP results, we develop a geophysical conceptual site model which can be used by site engineers to interpret/implement the findings for build-out. Our approach fills the gaps between the well data and geological model and suggests the most suitable places for the development of engineered structures in the hard rock terrains.